A preventive maintenance policy with usage-dependent failure rate thresholds under two-dimensional warranties. (2nd November 2021) - Peng, Shizhe; Jiang, Wei; Zhao, Wenhui
Abstract: This article considers Preventive Maintenance (PM) under a two-dimensional (2-D) warranty contract with time and usage limits. From a manufacturer's point of view, we develop a dynamic maintenance model with a random horizon to include the impact of random and dynamic usage rates on PM decisions. The model treats the cumulative amount of usage as a state variable that provides information about the failure rate and the expiration of the 2-D warranty. We characterize the optimal PM policy by a sequence of usage-dependent failure rate thresholds. Each threshold is a function of the cumulative usage. Our failure rate threshold policy chooses one of the following two actions in each period: performing perfect PM or no PM. Specifically, the manufacturer should bring the failure rate back to its original level when it exceeds the threshold in the corresponding period. This policy is also optimal under a constant usage rate. In the numerical experiments, we demonstrate the effectiveness of the proposed policy and conduct a sensitivity analysis to investigate how this policy is affected by the model parameters.